Pendekatan Diagnosis pada Pasien dengan Primary Sclerosing Cholangitis (PSC): Sebuah Laporan Kasus - I Putu Aris Govindha Putra; I Ketut Mariadi (MEDICINUS, 2026)
Primary sclerosing cholangitis (PSC) is a chronic, progressive cholestatic liver disorder of unknown etiology, characterized by inflammation, fibrosis, and narrowing of the intrahepatic and/or extrahepatic bile ducts. The discovery of commonclinical manifestations of cholestasis, whose etiology is difficult to determine, makes PSC cases a challenge for clinicians. We reported the case of a 20-year-old female who presented with the chief complaint of jaundice lasting 6 months.Symptoms included pruritus, tea-colored urine, pale stools, decreased appetite and body weight, and the appearance of bruising without trauma. The patient underwent several examinations, including laboratory tests, ultrasound, CT scan,and magnetic resonance cholangiopancreatography (MRCP), which showed a blockage and narrowing of the bile ducts. The first endoscopic retrograde cholangiopancreatography (ERCP) included biliary stent placement, but the complaints persisted, so a repeat ERCP was performed, revealing a biliary tract stricture. The initial diagnosis was PSC with severe acute cholangitis and coagulopathy. Patient was treated with antibiotics, steroids, and ursodeoxycholic acid (UDCA). In clinical practice, the recognition and confirmation of the diagnosis, as well as the management of PSC remain challenging. This case highlights the importance of early recognition and suspicion as well as comprehensive treatment of PSC to prevent further complications.